Spinal dural arteriovenous fistula: A rare but treatable disease that should not be missed by orthopedic surgeons - Yang, Baohui; Lu, Teng; He, Xijing; Li, Haopeng (Frontiers in Neurology, 2022)
Objective Spinal dural arteriovenous fistula (SDAVF) is a rare disease that is often misdiagnosed by orthopedic surgeons. We analyzed the reasons for the misdiagnosis and proposed countermeasures. Methods 22 SDAVF patients who were initially treated in orthopedics were included. The patients were divided into a correct diagnosis group (A) and a misdiagnosis group (B). The clinical data and prognosis were evaluated. Results There were 10 patients in group A and 12 patients in group B. The clinical manifestations included limb numbness, weakness, and bladder and bowel dysfunction. Among these patients without spinal degenerative diseases which had typical magnetic resonance imaging (MRI) features in Group A were more than Group B (P<0.05). More patients had spinal degenerative diseases in group B. In group A, 7 patients were primarily diagnosed with a SDAVF after multidisciplinary teamwork (MDT). In group B, 5 patients were misdiagnosed with lumbar spinal stenosis, 4 with lumbar disc herniation, 2 with thoracic spinal stenosis, and 1 with cervical spinal stenosis and lumbar spinal stenosis and underwent cervical spinal canal and lumbar spinal canal decompression. The length of time for confirming the diagnosis was 7 months longer in group B than in group A. All patients underwent microsurgery treatment. The average follow-up duration was 11 months. The modified Aminoff-Logue Disability Scale scores showed a statistically significant difference in improvement between the two groups (P<0.05). Conclusion when patients with dysuria especially, have intermittent spinal nerve dysfunction, the possibility of SDAVF should be considered. Awareness of the specific clinical and spinal cord edema and flow voids on MRI of a SDAVF needs to be promoted for orthopedic surgeons. Timely MDT is an important measure for reducing misdiagnosis, and steroids or inappropriate surgery should be avoided until a SDAVF is completely excluded.